INCOME ANALYSIS OF CURLY CHILI FARMING (CAPSICUM ANNUUML) IN THE RAINY AND DRY SEASONS (CASE STUDY: PT. INTIDAYA AGROLESTARI, BOGOR) - Armaeni Dwi Humaerah; Titik Inayah; Pahrul Rozy (AGRIBUSINESS JOURNAL, 2020)
PT Intidaya Agrolestari is a company engaged in the agricultural business.  One type of business is the curly chili farming business which is a type of business that has just been carried out and is in the development stage.  The constraints and constraints of seasonal factors in the production of curly chilies greatly affect the amount of output or harvest produced so it greatly affects the income of the farming business. The greater the output or harvest produced, the greater the income received. The objectives of this study are knowing the cost of farming curly red chili in the rainy and dry seasons. Knowing the income of the curly red chili farming business in the rainy season. Knowing the feasibility of farming curly red chili in the rainy and dry seasons by using the R/C ratio, B/C ratio, and Break Event Point (BEP).The results of this study show that the total cost of farming curly chili in the rainy season with a land area of 1 Ha, namely Rp. 128,574,400, is greater when compared to the total cost of farming curly chili in the dry season with a land area of 1 Ha, namely Rp. 117,691,400, -. The total income of curly chili farming in the rainy season with a land area of 1 Ha is Rp. 28,425,875, -greater than the income of curly chili farming in the dry season with a land area of 1 Ha which suffered a loss of Rp. 77,691,400. Analysis of the Income Level of curly chili farming in the rainy season with a land area of 1 Ha in terms of R/C ratio, B/C ratio, and BEP can be said to be feasible to continue. Because it obtained an R/C ratio value of more than 1, which is 1.22 B/C ratio of more than 0, which is 0.22, and has produced a total production of 5,627.25 kg, with a selling price of Rp. 27,900, each of which has passed the production BEP value of 4,608 kg and the BEP price value of Rp. 22,849. Meanwhile, the Income Level Analysis of curly chili farming in the dry season with a land area of 1 ha as seen from the R/C ratio, B/C ratio, and BEP can be said to be unfit. Because it obtained an R/C ratio of less than 1, namely 0.34, a B/C ratio of less than 0, which is -0.66, and has produced a total production of 1000 kg, with a selling price of Rp. 20,000, each of which does not exceed the limit of the production BEP value of 5,885 kg and the BEP price value of Rp. 58,846.